143k views
3 votes
5X+3(-2x-4)=3-4(X+3)

User RDM
by
5.5k points

2 Answers

3 votes

Answer: X= 1

Explanation:

Let's solve your equation step-by-step.

5x+3(−2−4)=3−4(x+3)

Step 1: Simplify both sides of the equation.

5x+3(−2−4)=3−4(x+3)

5x+3(−2−4)=3+(−4)(x)+(−4)(3)(Distribute)

5x+−18=3+−4x+−12

5x−18=(−4x)+(3+−12)(Combine Like Terms)

5x−18=−4x+−9

5x−18=−4x−9

Step 2: Add 4x to both sides.

5x−18+4x=−4x−9+4x

9x−18=−9

Step 3: Add 18 to both sides.

9x−18+18=−9+18

9x=9

Step 4: Divide both sides by 9.

9x/9 = 9/9

x=1

User Geetika
by
5.0k points
3 votes

Answer:

x=1

Explanation:

5x+-6-12=3-4x-12

+12 +12

5x -6=3-4x

+4x +4x

9x-6=3

+6 +6

9x=9

/9 /9

x=1

User Praveen Vinny
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.